Effective-Range-Expansion Study of Near Threshold Heavy-Flavor Resonances. (16th June 2019) - Gao, Rui; Guo, Zhi-Hui; Kang, Xian-Wei; Oller, J. A.
Abstract : In this work, we study the resonances near the thresholds of the open heavy-flavor hadrons using the effective-range-expansion method. The unitarity, analyticity, and compositeness coefficient are also taken into account in our theoretical formalism. We consider theZ c ( 3900 ), X ( 4020 ), χ c 1 ( 4140 ), ψ ( 4260 ), andψ ( 4660 ) . The scattering lengths and effective ranges from the relevant elasticS -wave scattering amplitudes are determined. Tentative discussions on the inner structures of the aforementioned resonances are given.